Synthesis of h-BN by the Combustion of B/KNO3/Octogen Mixture under Nitrogen Atmosphere - Song-qi Hu; Yin Wang; Lin-lin Liu (Journal of Chemistry)
Hexagonal boron nitride (h-BN) powders were fabricated by the combustion synthesis with B/KNO3/HMX (octogen) mixtures as reactants. X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were adopted to investigate the phase composition and the chemical composition of the products, respectively. The morphology and resistance to oxidation were studied by scanning electron microscopy (SEM) and thermogravimetry (TGA), respectively. The characterization results showed that the h-BN which was produced through this method has high purity and exhibits excellent resistance to oxidation. The purity of h-BN is improved with the increasing content of HMX in reactants with boron carbide (B4C) and boron oxide (B2O3) as main impurity, but conversely, the yields are obviously decreased. Taking the comprehensive consideration of the purity and the yields together, the optimal molar ratio of B/KNO3/HMX is 10 : 1 : 4. In addition, the experimental results indicated that the crystalline grain size grows with the increasing content of HMX. The method explored in this study does not need expensive processing facilities and equipment, which is a preferable approach for the laboratory to prepare h-BN of high purity.